Lulu and the rabbit next door - McKay, Hilary (McKay, Hilary. LuLu., 2012)
Lulu has a new next-door neighbor named Arthur and he has a pet rabbit. Of course Lulu must become their friend. But Arthur doesn't seem to want to be her friend. Or play with his rabbit. It's up to Lulu and Mellie to come up with a plan to make Arthur see just how fun rabbits can be.